种储能电压平衡电力电子电能变换系统及其控制方法 (2018)
本发明提供种储能电压平衡电力电子电能变换系统及其控制方法，包括储能模组、电压平衡变换器、电网侧逆变器、电网负荷、储能侧逆变器和独立负荷。该电能变换的控制方法包括独立电压平衡变换器的控制方法、电压平衡变换器的控制方法和单相级联逆变器的移相控制方法。通过对高频软开关电压平衡变换器的控制，实现储能模组的均衡控制、延长储能设备的使用寿命并降低使用成本，同时，为电网侧逆变器提供多路隔离直流电压。通过该电能变换系统对储能模组进行充放电，实现储能与电网的电气隔离，并与电网形成互动，实现消峰填谷、谐波治理、无功补偿和三相不平衡调整。本发明通过模块化设计实现，具有电网和储能侧电气隔离、控制简单、体积小、效率高、成本低和可靠性高等特点。 The invention provides an energy-storage voltage-balanced power electronic electric energy converting system and a control method thereof. The energy-storage voltage-balanced power electronic electric energy converting system is composed of an energy storage module, a voltage-balanced converter, a power-grid-side inverter, a power grid load, an energy-storage-side inverter and an independent load. Through control over the high-frequency soft-switching voltage-balanced converter, balanced control over an energy storage unit or module is realized, the service life of energy storage equipment is prolonged, the use cost is reduced, and meanwhile, multiple routes of isolation direct voltage are provided for